Design Of Automatic Laptop Cooling System Using Ds18b20 Temperature Sensor Based On Arduino Nano - oktrison Oktrison; Erwinsyah Sipahutar; Rudi Arif Candra; Arie Budiansyah (Brilliance: Research of Artificial Intelligence, 2025)
Technological developments in the field of automation provide opportunities to improve efficiency and comfort in the operation of electronic devices. This research aims to design and implement an automatic cooling system on a laptop that uses an Arduino Nano-based DS18B20 temperature sensor. The system is designed to automatically regulate the laptop temperature by monitoring the temperature in real-time, and activating the cooling fan through a relay when the temperature reaches 33°C or more. This research method includes hardware design that involves the use of Arduino Nano as a microcontroller, a DS18B20 temperature sensor to detect temperature changes, and a relay to control the cooling fan. The software was developed using the Arduino programming language (C++) to process the data from the sensors and manage the work of the cooling system automatically. The test results show that the system can accurately detect the laptop temperature and respond in real-time by turning on the cooling fan when the temperature exceeds the 33°C limit. The system proved to be effective in preventing overheating, keeping the device temperature within safe limits, and optimizing power consumption by turning off the fan when the temperature returns to stable.